STRATEGI GERAKAN PENERAPAN SYARIAT ISLAM FRONT PEMBELA ISLAM DI MOJOKERTO - Mujibuddin, Mujibuddin (JPP (Jurnal Politik Profetik), 2021)
This study aims to analyze the movement for the application of Islamic law by the Islamic Defenders Front (FPI) in Mojokerto. Mojokerto is a city with strong NU tradition roots as NU Mojokerto is one of the largest Islamic organizations in this city. So far, NU Mojokerto has never carried out acts of violence in the name of religion. However, the strong tradition of NU does not guarantee the development of radical issues in Mojokerto. This study tries to analyze the strategy of mass networking as well as its efforts in implementing Islamic law in Mojokerto. This research is a field study that uses political opportunity theory to analyze the movement. Based on the research, the author found that there were two strategies undertaken by FPI to implement Islamic law in Mojokerto. First, FPI uses democracy to support candidate leaders who are on the same mission as them. In addition, FPI also encourages society to choose a leader who supports the implementation of Islamic law.  Secondly, FPI takes an action in doing the raid in particular places around the city. The political opportunities that have opened since the reformation era have made it easier for FPI to mobilize the masses, FPI has the freedom to express its opinion in various actions.